Penguatan Kompetensi Guru PAI melalui Penggunaan Instruction in English - Nurhayati, Sri - (IAIN Madura, 2019)
The development of English as international language requests for bigger requirements in all aspects of life, especially education field. Automatically, teachers are supposed to have English competence in keeping up the students? development. Islamic education teachers (PAI) are suggested to use English in teaching or at least they use English in giving instruction in the classroom. Since this way of teaching is as one of the requirements of an international school. This way is also supporting the school in gaining the people?s trust. The strategy used in empowering the Islamic education teachers in teaching using English is set in a form of community engagement (PKM). The schools chosen are all school under the Asyahidul Kabir institution from the Islamic elementary school, Islamic junior high school, and Islamic senior high school. This engagement is divided into two sessions. First session is for the educating session and the second one is for the practice. For the educating sessions, it is clearly seen that instruction in English help the teacher very much, although the pronunciation still needs to be corrected. While in the practice session, they are still nervous in using some instruction because they have to teach their friends in peer teaching. But overall the sessions ran well. When the facilitator passed these two sessions, she will do some observation on the Islamic education classroom to ensure that they have practiced using English in giving instruction well. The result from the observation show that the weakness of the teacher is in the preparing stage. The teachers still need to pay more attention on the students? need and students? readiness.